Evaluación productiva en toretes de engorde enteros y castrados estabulados alimentados con pasto king-grass y concentrado en el cantón Antonio Elizalde de la provincia del Guayas” - Torres Romero, Mónica Mercedes (2012)
The present research was conducted in the Rancho Hacienda Elena, located in Canton General Antonio Elizalde, Bucay, of the Province of Guayas, whose objective was to evaluate the production of fattening bulls housed integers and grass-fed castrated King-Grass and concentrated. Two groups, steers of 24 months, ten integers five grass-fed grass-fed five King - Grass more concentrated, ten castrated five grass-fed grass-fed five King - Grass more concentrated, the data were evaluated Factorial design by Random 2x2. GDP range of total was 477 and 579 g per day, equivalent to 1.05 and 1.27 lb per day over the period of 161 days, the range of total weight gain was 77 to 93 kg per UA. The analysis of variance of the four groups determined that there was no statistical significance between the averages of the weights, (p  0.05) and (p  .01)..........